Dinamika Minat Beli Konsumen Pada Produk Skincare Khaf: Pengetahuan Produk Dan Perceived Value Menjadi Pengaruh: Studi Kasus Pada Mahasiswa Dehasen - Harsen Subakti; Andi Azhar (PT. Karya Inovatif Nusantara, 2025)
This study aims to examine the influence of product knowledge and perceived value on consumer purchase intention for Khaf skincare products among students at Universitas Dehasen. The research employs a quantitative approach using a survey method with 120 students as respondents, selected through purposive sampling. The results indicate that product knowledge has a positive and significant influence on consumer purchase intention, with a regression coefficient of 0.318. Additionally, perceived value also has a significant influence, with a regression coefficient of 0.590. Product knowledge was found to have a more dominant effect on purchase intention compared to perceived value. These findings highlight the importance of consumer education regarding product quality and benefits as a key marketing strategy. This study contributes to local skincare companies, particularly in developing effective marketing strategies to enhance competitiveness in the market.